Misrepresentation of Science and Expertise: Reflecting on Half a Century of Indonesian Anthropology - Irwan Abdullah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Indonesian anthropology was founded in 1957 and developed since then in various universities. After more than fifty years of inhabiting these lecture halls, anthropology’s orientation as a science has transformed from a discipline that bestows on graduates the ability to think into one in which graduates are prepared for a career of conductingfield research ordered by others. This article reflects on the shifts that have occurred in anthropology, focusing on three of the field’s central figures in Indonesia: Koentjaraningrat, Masri Singarimbun, and Parsudi Suparlan. During the lives of these three pioneers, anthropology playeda central role in critically evaluating humanitarian projects, and as such anthropologists frequently served to protect the weak and marginal. Anthropologists were on the frontlines of every discussion regarding the future of the nation, enabling anthropological perspectives to be accommodated in policy. Today, anthropologists seem locked into their own academic spaces. The results of anthropological field research are often said to provide unique and interesting—but irrelevant—stories. This article recommends a fundamental transformation in the curriculum, allowing the politics of science to be reconsidered and reformulated to ensure anthropology maintains a central role in resolving future humanitarian problems.